(untitled) (Journal Of Educational and Psychological Researches, 2022)
The study aims to identify the concept of empowering women from the point of view of experts in the Palestinian society, specifically in Gaza, as well as to explore the foundations of their formation of this concept. Additionally, the study seeks to clarify the most important challenges facing the empowerment of women in Palestinian society. The study used the design of a grounded theory that seeks to build the theory through deep analysis of the data, as qualitative data were collected through holding two focus groups and six in-depth interviews with the study sample, who were selected by the method of targeted sampling. The sample included (16) individuals (9 female experts, 7 male experts) holding academic and community leadership positions. The results of the study showed that the concept of empowering women includes three dimensions related to enhancing women’s self-confidence, developing capabilities of self-realization awareness of women about rights, and how to achieve these rights. The concept of empowering women relied on basic principles, the most important of which are: the Islamic religion, the culture of the society, the requirements of reality, and successful experiences. The empowerment of women in Palestinian society faces challenges, the most prominent of which is the negative side in the society’s culture and the complexities of the Palestinian reality.